Managing pests and diseases of litchi for quality production - Kumar, Vinod; Nath, Vishal (Indian Horticulture, 2019)
Litchi contributes significantly to the growers’ economy in Bihar, West Bengal, Asom, Jharkhand and Uttarakhand in India. Several pests and diseases attack litchi and reduce the production and quality. Correct diagnosis is the key to right management decision. By prompt monitoring in orchard, adoption of Integrated Pest Management (IPM) as well as Good Agricultural Practices (GAP), all the pests and diseases can be managed and losses can be minimised.